The factory system illustrated : in a series of letters to The Right Hon. Lord Ashley - together with a narrative of the experience and sufferings of William Dodd, a factory cripple, written by himself /: in a series of letters to The Right Hon. Lord Ashley - together with a narrative of the experience and sufferings of William Dodd, a factory cripple, written by himself. (2018) - Dodd, William, 1804-
No abstract available